Is There Business Potential for Sustainable Shipping? Price Premiums Needed to Cover Decarbonized Transportation - Schwartz Henry; Solakivi Tomi; Gustafsson Magnus (MDPI, 2022)
The shipping sector is encountering remarkable costs concerning decarbonization of the maritime business. Both the International Maritime Organization and the European Union are developing tools to limit greenhouse gas emissions of shipping. Given all the tools and planned regulations, it seems that energy efficiency and cost cutting would be a feasible strategy of the future. However, in addition to cost cutting, shipping with net-zero or zero emission fuels might be a way to promote sustainable shipping services. A growing consumer segment is ready to pay for sustainability-marketed consumer goods, and it is possible that people would be ready to pay for net-zero or zero emission shipping as well. Our objective is to pinpoint, how big price premiums would be needed to cover the costs of shipping with sustainable, and typically more expensive, maritime fuels. We do this by calculating the amounts of fuel needed to ship specific good categories at first, and then we estimate the costs of shipping these goods with alternative fuels. We analyze Finnish maritime foreign trade during the year 2018, the time prior to the outbreak of COVID-19 pandemic. We estimate fuel consumption to the value and quantities of goods. Our findings indicate that a shift to low carbon and carbon neutral fuels would have a limited effect to the price of most goods.